Adolescent pregnancy trends in the last decade - Monteiro,Denise Leite Maia (2019)
SUMMARY INTRODUCTION Teenage pregnancy is a universal phenomenon, with higher prevalence in developing countries. Although there has been a reduction in Brasil since the year 2000, the age-specific fertility rate for this age group remains high. OBJECTIVE To evaluate the frequency of adolescence pregnancy in in Brasil from 2006 to 2015 and its association with the Human Development Index (HDI). METHODS A descriptive epidemiological study, conducted by searching the database of the Department of Informatics of the Unified Health System (DATASUS), using information from the Information System on Live Births (SINASC) for the five Brazilian regions. RESULTS There was a reduction in the percentage of live births (LB) from adolescent mothers (10 to 19 years old) in Brasil by 13.0% over the last ten years. This decline was observed in all Brazilian regions among mothers aged 15 to 19 years. The number of LB increased by 5.0% among mothers aged 10 to 14 years in the North and decreased in the other regions, with higher rates in the South (18.0%). The specific fertility rate for the 15-19-year-old group decreased from 70.9/1,000 to 61.8/1,000 in the period. The proportion of LB is inversely associated with the HDI, except in the Northeast (the lowest HDI in the country), where there was a significant reduction (18.0%) among mothers aged 15-19 and 2% among those aged 10-14 years. CONCLUSION Teenage pregnancy in Brasil is in slow decline, especially among mothers aged 10-14 years and is inversely associated with the HDI, except in the Northeast.